Reconstruction of Low Speed Rear-End collisions - Technical Means of Assessing Cervical Spine Injuries - Martin Hitzemann (Pain Research and Management)
In recent years, an increasing number of cervical spine injuries sustained by vehicle occupants in collisions at comparatively low speeds have been reported to insurance companies and in civil litigation. The reported injuries occur in both rear-end and side impact collisions. The paper describes how a detailed assessment of such cases requires interdisciplinary teamwork involving technical, biomechanical and medical experts.